A Review on Nepalese Medicinal Plants Used Traditionally as Alpha-Amylase and Alpha-Glucosidase Inhibitors Against Diabetes Mellitus - Shrestha, Dipesh; Sharma, Prabha; Adhikari, Achyut; Mandal, Ashok K.; Verma, Amita (Current Traditional Medicine, 2021)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia in which the blood sugar levels are increased. Nepalese medicinal plants are being used traditionally since long back in the treatment of diabetes. These plants have provided a broad research area in modern medicine development due to their potency to inhibit digestive enzymes. The isolated compounds and crude extract of these plants exhibited the property of inhibiting the digestive enzymes (α-amylase and α-glucosidase). Objective: This review's primary purpose is to explore the inhibitory activity of Nepal's medicinal plants against the digestive enzymes (α-amylase and α-glucosidase) as a practical approach to control type-2 diabetes mellitus (T2DM). Twenty Nepalese medicinal plants belonging to 19 families and compounds isolated from them possessing potent inhibitory activity against digestive enzymes and are responsible for managing postprandial hyperglycemia are reviewed under this article. Methods: The scientific evidence of the tabulated medicinal plants' function in managing postprandial hyperglycemia through inhibition of digestive enzymes (α-amylase and α-glucosidase) was carefully investigated online. As a result, searches in PubMed, Research Gate, and Google Scholar were conducted. All of the data from the various sources have been organized in a structured manner. Results and Conclusion: From the database available, twenty plants with their crude extract and some isolated compounds and their IC50 values are tabulated. Thus, these compounds could be vital components in drug design with fewer side effects and could be a replaceable agent to conquer diabetes threats.
Keywords: Diabetes mellitus